A new species of the New Caledonian endemic genus Xanthochorema Kimmins, 1953 (Insecta: Trichoptera: Hydrobiosidae) - Johanson, Kjell Arne (Zootaxa, 2002)
Xanthochorema neocaledonia sp.n.is described from New Caledonia, raising to seven the number of Hydrobiosidae (Trichoptera) species now known from New Caledonia. A key for discrimination of males of these seven species is presented, and distributional maps are included for all species. In addition, new records are included for Xanthochorema bifurcatum Schmid, 1989, Xanthochorema calcaratum Schmid, 1989, and Xanthochorema celadon Schmid, 1989.